Viscoelastic damping in crystalline composites: A molecular dynamics study - Ranganathan, Raghavan; Ozisik, Rahmi; Keblinski, Pawel (Composites. Part B, Engineering, 2016)
Molecular dynamics (MD) simulations were used to study viscoelastic behavior of model Lennard-Jones (LJ) crystalline composites subject to an oscillatory shear deformation. The two crystals, namely a soft and a stiff phase, individually show highly elastic behavior and very small loss modulus. On the other hand, when the stiff phase is included within the soft matrix as a sphere, the composite exhibits significant viscous damping and a large phase shift between stress and strain. In fact, the maximum loss modulus in these model composites was found to be about 20 times greater than that given by the theoretical Hashin-Shtrikman upper bound. We attribute this behavior to the fact that in composites shear strain is highly inhomogeneous and mostly accommodated by the soft phase. This is corroborated by mode-dependent Grüneisen parameter analysis showing that in the low frequency regime, Grüneisen parameters, which measure degree of anharmonicity, are about twice greater for the composite than each individual homogenous crystal. Interestingly, the frequency at which the damping is greatest scales with the microstructural length scale of the composite, a feature we also observe for superlattice structures.